MANAJEMEN PENGAWASAN PERATURAN DAERAH DILAHAT DARI PERUNDANGAN-UNDANGAN - Hotman Napitupulu (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
Management of regulatory oversight under the law, analyze the legal consequences with its use as a system of legal oversight mechanisms in order to create harmonization of law in the region. As for the method used in research by using empirical method that is by conceptual approach method with primary and secondary data source. As for the method used in research by using empirical method that is by conceptual approach method with primary and secondary data source.